Reverse Phase High Performance Liquid Chromatographic Determination of Gatifloxacin in Gatifloxacin Eye Drops - Shirke, T.R.; Pai, Nandini (Asian Journal of Chemistry, 2010)
A simple and precise reverse phase HPLC method was developed for the estimation of gatifloxacin in ophthalmic formulations. The method was carried out on a Thermoquest C8 (15 cm x 4.6 mm i.d., 5 μ) column with mobile phase consisting of buffer monobasic potassium phosphate 4.0827 g diluted to 1 L in the proportion Buffer : acetonitrile : triethylamine ( 650 : 350 : 2 ) mixed properly and 2 g of sodium lauryl sulphate was added. pH was adjusted to 3.0 with orthophosphoric acid at a flow rate 1.5 mL/min. Detection was carried out at 290 nm. The retention time of gatifloxacin was 10.9. The validation of the proposed method was also carried out.